Impact of instructional intervention program upon women’s psychological health status who undergo chemotherapy after mastectomy - Ibrahim, nuha; ali, Rabia (Iraqi National Journal of Nursing Specialties, 2012)
Objective(s): To determine the impact of instructional intervention program upon psychological health status for women who undergo chemotherapy after mastectomy Methodology: The sample consisted of (100) women, (50) considered as study group, and another (50) the control group. A pre test was done for both groups (study and control), and then the study samples were exposed to an instructional intervention and three-dimensional post tests and the length of time between each test 21 days in the Institute and Hospital of Radiation and Nuclear Medicine. The questionnaire composed of three parts, first, demographic information; include (age, educational level, type of family, occupation, marital status, and adequacy of monthly income). Second, information about breast cancer include (the period in which the disease was diagnosed, the type of breast cancer, method of chemotherapy administration, the period of the chemotherapy, the order of the current session of chemotherapy treatment, the number of chemotherapy sessions, the source of information of chemotherapy side effects. Information on previous medical history and consists of (the previous problem of the breast, the type of injury, the site of disease, type of surgery, stage of the cancer when it was discovered, family members who suffer from breast cancer). Third, the psychological effects. Pre and post test was used to determine the reliability of the questionnaire with a time interval for a period of more than 3 weeks between each test, the results (r = 0.9013) for the psychological effects. Analysis of data was performed through the application of descriptive and inferential statistical data analysis approach. Results: Revealed that there is lack of information in women treated with chemotherapy after mastectomy before the implementation of the program regarding the side effects of chemotherapy treatment, and the symptoms which appear on patients increase their anxiety and negative psychological symptoms but after the implementation of the program the information of women become well and their psychological status improved. Recommendations: the study recommended that the Institute and Hospital of Radiation and Nuclear Medicine must include an instructional intervention program concerning the psychological health of women who are treated with chemotherapy after mastectomy